Valproate-associated reversible encephalopathy in a 3-year-old girl with Pallister-Killian syndrome - Gerstner, Thorsten (Dove Medical Press, 2008)
Valproic acid (VPA) is considered to be a drug of first choice for the therapy of generalized and focal epilepsies, including special epileptic syndromes. The drug is usually well tolerated, rare serious complications may occur in some patients, including hemorrhagic pancreatitis, coagulapathies, bone marrow suppression, VPA-induced hepatotoxicity and encephalopathy. We report a case of VPA-associated encephalopathy without hyperammonemia in a 3-year-old girl with Pallister-Killian-Syndrom, combined with a mild hepatopathy and thrombopathy. After withdrawal of VPA, the clinical symptoms and the electroencephalography-alterations vanished rapidly.